2006
DOI: 10.1007/s11882-996-0015-6
|View full text |Cite
|
Sign up to set email alerts
|

Mite immunotherapy

Abstract: Dermatophagoides pteronyssinus and D. farinae are the most common house dust mites and are among the most common sources of indoor allergens worldwide. These species are very common in humid regions, where most allergic individuals are sensitized to house dust mites. Specific immunotherapy with mite extracts has demonstrated clinical benefits in several double-blind, placebo-controlled trials that are included in recent reviews of subcutaneous immunotherapy, including pediatric and adult patients with rhinocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 71 publications
1
9
0
1
Order By: Relevance
“…Patients who are exposed to large quantities of mite allergens may experience a progressive deterioration in PD 20 FEV 1 . This fact is consistent with a chronic inflammatory and remodeling process of the lungs, as has been suggested for several animal models, including rhesus monkeys, sheep and mice [12] . There is ample evidence that continuous exposure to mites is an important risk factor for the development of sensitization, allergic respiratory diseases and chronic inflammation of the lungs.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Patients who are exposed to large quantities of mite allergens may experience a progressive deterioration in PD 20 FEV 1 . This fact is consistent with a chronic inflammatory and remodeling process of the lungs, as has been suggested for several animal models, including rhesus monkeys, sheep and mice [12] . There is ample evidence that continuous exposure to mites is an important risk factor for the development of sensitization, allergic respiratory diseases and chronic inflammation of the lungs.…”
supporting
confidence: 89%
“…However, in light of publications that have shown pessimistic results using environmental control measures, immunotherapy with mite extracts has emerged as a solid treatment of mite-induced allergic respiratory diseases. Numerous studies have shown the efficacy of mite sublingual and subcutaneous immunotherapy [12] . The future treatment of mite-induced allergies will not be changed much, although it will be based on a more accurate diagnosis and better immunotherapy treatments.…”
Section: Mite Immunotherapymentioning
confidence: 99%
“…All tested antibiotics suppressed the Bartonella -like bacteria, and neomycin and streptomycin suppressed Cardinium . This findings should be useful in production of mites for medical diagnostics (purified natural allergens) and immunomodulations [50], [51]. However, Solitalea -like associated group was not influenced by treatment with the antibiotics used here.…”
Section: Discussionmentioning
confidence: 61%
“…The polymerisation process reduces the IgE-binding capacity of the extract, thus reducing its allergenicity [5,6,7,9,34,35]. DPP extract did not induce high levels of IgE even when formulated in combination with AlOH, an adjuvant that boosted IgE levels when adsorbed onto N extract.…”
Section: Discussionmentioning
confidence: 99%